ADAPTASI MODEL DELONE DAN MCLEAN YANG DIMODIFIKASI GUNA MENGUJI KEBERHASILAN IMPLEMENTASI APLIKASI OPERASIONAL BAITUL MAAL WAT TAMWIL (BMT) BAGI INDIVIDU PENGGUNA (Studi Empiris Pada BMT di Kota Semarang) - Novita Anugrah Listiyana; Dedi Rusdi (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2015)
This study analyzed the relationship between humans as users of the system and application software as object an inseparable relationship. The purpose of this study was to analyze the effect of variable quality system to the perception of the quality system, the effect of perceived quality system and quality of information on the intensity of use and user satisfaction, and the influence of the intensity of use and user satisfaction of the impact of individual performance. This research is an empirical study using purposive sampling technique in data collection. Data were collected through questionnaires to 39 BMT’s operational employees. Then, performed an analysis of the data obtained used path analysis. This included: testing hypotheses through path analysis. The results of tests performed using path analysis to get the results that each variable in the model of equation 4 had a coefficient with a positive direction. This means that the improvement of the quality of the system will be able to improve the quality of information for the individual impact of the use and satisfaction of employees through the use of the system.